Characteristics of Occlusal Force and Masticatory Performance in Female Patients Who Selected Implant Treatment for a Missing Mandibular Second Molar: A Retrospective Study - Takashi Abe; Motohiro Munakata; Takumi Yokoi; Kikue Yamaguchi; Daisuke Sato; Kazuyoshi Baba (Journal of Functional Biomaterials, 2025)
Background: In this study, we aimed to investigate the association between a patient’s selection of implant treatment for a missing mandibular second molar and the magnitude of occlusal force, masticatory ability, mandibular morphology, and age before treatment intervention. Materials and Methods: We retrospectively assessed occlusal force, masticatory performance, and mandibular morphology in female patients who either selected or declined implant treatment for a missing unilateral mandibular second molar. Results: Thirty-three women (mean age of 56.1 ± 9.7 years) were divided into an implant treatment (IT) group and a no-treatment (NT) group. The IT group showed significantly higher occlusal force (p = 0.021 < 0.05), while masticatory performance and gonial angle demonstrated no significant difference. Conclusion: The IT group had significantly higher occlusal force, and age had no significant effect on it. Notably, masticatory performance in the IT group increased significantly with age (p = 0.047 < 0.05).